2015
DOI: 10.2147/ndt.s87014
|View full text |Cite
|
Sign up to set email alerts
|

Serum 25-hydroxyvitamin D predicts cognitive performance in adults

Abstract: BackgroundVitamin D is an endogenous hormone known to regulate calcium levels in the body and plays a role in cognitive performance. Studies have shown an association between vitamin D deficiency and cognitive impairment in older adults. Lebanon has a high 25-hydroxyvitamin D (25(OH)D) deficiency prevalence across all age groups.MethodsIn this cross-sectional study, we explored the cognitive performance and serum 25(OH)D levels using an electrochemoluminescent immunoassay in 254 older (>60 years) as well as yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 38 publications
1
38
0
Order By: Relevance
“…There is a known association between 25 (OH)D levels and cognitive performance151819 in older adults, but the relationship between 25 (OH)D and cognition in MS patients has not been explored. In this report, we show that a relatively short course of oral supplementation with vitamin D 3 in MS patients deficient in serum 25 (OH)D, improved memory as measured by the BVMT Delayed Recall and MoCA (general memory test that includes long term as well as visuo-spatial memory).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a known association between 25 (OH)D levels and cognitive performance151819 in older adults, but the relationship between 25 (OH)D and cognition in MS patients has not been explored. In this report, we show that a relatively short course of oral supplementation with vitamin D 3 in MS patients deficient in serum 25 (OH)D, improved memory as measured by the BVMT Delayed Recall and MoCA (general memory test that includes long term as well as visuo-spatial memory).…”
Section: Discussionmentioning
confidence: 99%
“…The impairment affects a wide range of cognitive functions including verbal and non-verbal memory, and information processing speed12. Studies in humans provide support for a role of the vitamin D in cognitive functioning, and recent studies have linked low serum 25 (OH)D levels to cognitive dysfunction in adults131415. Vitamin D receptors are expressed by neurons and glial cells1617 supporting a role for vitamin D beyond bone homeostasis.…”
mentioning
confidence: 99%
“…Increasing the behavioral and cognitive function would increase outdoor activities and exposure to sunlight [1,48]. Different studies had reported that insufficiency or deficiency of vitamin D is associated with cognitive impairment [1,23,[53][54][55][56]. Vitamin D deficiency can be associated with muscle weakness that might lead to cognitive impairment [57].…”
Section: Discussionmentioning
confidence: 99%
“…We couldn't detect any association between the total PANSS score and its three subscales with vitamin D deficiency (p>0.05). Lebanon has a high prevalence of 25(OH)-D deficiency in adults and older adults [23,24] however, data regarding vitamin D levels in psychiatric patients is still lacking. Therefore, the primary objective of this study was to compare the vitamin D status in schizophrenics to that of healthy controls; secondary objectives were to assess the…”
Section: Methodsmentioning
confidence: 99%
“…Correction of vitamin deficiencies is known to be essential; for example, vitamin D deficiency is common in the general population, and this deficiency may exacerbate inflammation and cognitive decline 139,140 . Thyroid function should be checked and any deficiency should be treated, as thyroid deficiency can lead to cognitive decline 141 .…”
Section: Management Of Fxtasmentioning
confidence: 99%